2011
DOI: 10.1002/ar.21445
|View full text |Cite
|
Sign up to set email alerts
|

The Third Branch of the Main Trunk of the Left Coronary Artery in Cercopithecus aethiops sabaeus. Is the Nonhuman Primate Model Appropriate?

Abstract: The aim of this study was to investigate the morphometry of branching patterns of the main trunk of the left coronary artery (MT of LCA) in nonhuman primates, and comment on the current nomenclature. The biometric study was performed using stereomicroscopic dissection of hearts of healthy and fertile nonhuman primates (Cercopithecus aethiops sabaeus) of both sexes. Our results reveal that the MT of LCA terminates in a bifurcation into the anterior interventricular branch (AIB) and the circumflex branch (CB) (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The findings of this study showed that in the trifurcation pattern, the LCA has a longer mean length than the bifurcation pattern. The present study confirms the findings of Nikolic et al (2011) who stated that the mean length of LCA is longer in trifurcation than in bifurcation pattern. However, it could not validate the association between the lengths of the LCA and its branching pattern due to the small sample size of the quadrifurcation pattern in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study showed that in the trifurcation pattern, the LCA has a longer mean length than the bifurcation pattern. The present study confirms the findings of Nikolic et al (2011) who stated that the mean length of LCA is longer in trifurcation than in bifurcation pattern. However, it could not validate the association between the lengths of the LCA and its branching pattern due to the small sample size of the quadrifurcation pattern in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Its presence reduces risk of atherosclerosis of left anterior interventricular artery and circumflex coronary artery. Median artery is a constant feature of rabbit, monkey, squirrel monkey and pig hearts [ 15 ]. In conclusion the incidence of closed type of trigone with median artery as a predominant content is found in maximum hearts.…”
Section: Discussionmentioning
confidence: 99%
“…The blood supply to the sterno-costal surface of the left ventricle may be through an ATB [16]. It may also give off 1 or more anterior septal arteries and supply the anterior papillary muscle of the left ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…It may also give off 1 or more anterior septal arteries and supply the anterior papillary muscle of the left ventricle. In certain cases, and depending on its distribution, the ATB may be an important source of collateral circulation [16,24]. The identification of this vessel may be of clinical importance because the extent of its supply may decrease the effect of occlusion of the AIA and LCx artery on the myocardium [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation